Development of a potential challenge model and plant-produced vaccine candidate for beak and feather disease virus - Regnard, Guy Louis (Department of Molecular and Cell Biology, 2015)
Psittacine beak and feather disease (PBFD), the most prevalent viral disease affecting psittacines, is caused by beak and feather disease virus (BFDV). An outbreak of the disease has been reported in wild endangered Cape parrots (Poicephalus robustus), which is endemic to South Africa. No treatment or vaccine is commercially available. In this study, an investigation into the outbreak was undertaken. BFDV diversity was assessed and viral load and clinical signs correlated. A plant-produced BFDV subunit vaccine was produced in parallel with a corresponding challenge model. Cape parrots were assessed and 53 blood samples collected. Viral load was determined using quantitative real-time PCR (qPCR), and 22 BFDV full-length genome sequences acquired to infer phylogenetic relatedness. The capsid gene (cp) was optimised for transient Agrobacterium-mediated expression in whole-plant Nicotiana benthamiana (N. benthamiana). Virus-like particles (VLPs) were purified and analysed using transmission electron microscopy. Virions from a Palm cockatoo (Probosciger aterrimus) were purified and a BFDV dsDNA molecular clone was synthesised and replication assessed in 293TT mammalian cells and N. benthamiana using rolling circle replication and qPCR. Two distinct BFDV phylogenetic clusters were reported for Cape parrots, and a direct correlation was seen between viral load in the blood and clinical signs in PBFD-afflicted birds. The CP was successfully expressed in N. benthamiana, and increased through optimisation of Agrobacterium infiltration density and the inclusion of the NSs silencing suppressor. The CP formed VLPs, which were shown to be morphologically similar to infectious virions. The dsDNA molecular clone was shown to replicate autonomously in mammalian 293TT cells, and in plants with the assistance of the Bean yellow dwarf virus replication associated protein (Rep). BFDV genetic diversity in Cape parrots highlights the importance of ensuring new strains are not inadvertently introduced into the wild. This is the first systematic investigation of virus diversity in Cape parrots and assessment of BFDV viral load in a wild psittacine population. The CP was successfully produced in planta and presence of VLPs suggests the possibility of developing pseudovirions. This is the first reported replication of BFDV in tissue culture, and will greatly expand the scope of available research.